The political economy of green growth in India - Payal Banerjee; Atul Sood (United Nations Research Institute for Social Development (UNRISD), 2012)
Rapid economic growth in India during the last two decades has accentuated the demand for energy and natural resources related to water, land and forests. Based on a review of the current policy framework in these areas and data from fieldwork in the northeastern region of India, this paper addresses two inter-related themes: (i) how emerging economies like India have dealt with the question of access to resources in response to the opposing demands of 'inclusive growth' and more equitable development aimed at closing 'social divides'; and (ii) the specific case study of two seemingly contradictory development trajectories, namely the 'Green Mission' and hydroelectric power (HEP) dams on the river Teesta in India's northeastern Himalayan region. The authors' review of the policy agenda for water, land, forests and river dams suggests that current approaches toward growth have largely privileged a mainstream development perspective, promoted privatization and often aggravated existing social inequalities. The effectiveness of the so-called 'green' or sustainable development approaches has largely been compromised due to their mainstream and increasingly neoliberal orientation conceptualized within a primarily techno-bureaucratic policy framework. Data presented in this paper reveal that communities living within or adjacent to sites of conventional modes of development, such as HEP projects, have experienced displacement, loss of livelihood, social conflict and rapidly depleting natural resources. These socioeconomic and environmental problems have continued to replicate themselves in different parts of India despite a notable presence of the rhetoric of sustainability in policy documents on energy and responsible resource management at the national level. Following this analysis, the paper proceeds to draw attention to some of the current challenges and questions for policy making that fast-growing developing economies like India face...
Keywords: 330